2015
DOI: 10.1017/s0950268815000023
|View full text |Cite
|
Sign up to set email alerts
|

Rapid spread of Clostridium difficile NAP1/027/ST1 in Chile confirms the emergence of the epidemic strain in Latin America

Abstract: Clostridium difficile infection has gained importance in recent years as a result of the rapid spread of epidemic strains, including hypervirulent strains. This study reports the molecular epidemiology of C. difficile obtained from hospitalized patients in Chile. Seven hundred and nineteen isolates of toxigenic C. difficile from 45 hospitals across the country were characterized through toxin profile, pulsed-field gel electrophoresis (PFGE), and sequencing of the tcdC gene. In addition, polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 14 publications
2
22
0
1
Order By: Relevance
“…3 Reporting clinical outcomes provides an opportunity to assess the safety and potential benefits of reducing unnecessary antibiotic use. A few studies showed no change or a decrease in Clostridium difficile infection and antibiotic-resistant pathogens, which are important metrics for assessing the patient-level impact of antibiotic stewardship.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Reporting clinical outcomes provides an opportunity to assess the safety and potential benefits of reducing unnecessary antibiotic use. A few studies showed no change or a decrease in Clostridium difficile infection and antibiotic-resistant pathogens, which are important metrics for assessing the patient-level impact of antibiotic stewardship.…”
Section: Resultsmentioning
confidence: 99%
“…This epidemic strain was also reported in Asia, providing evidence of worldwide spread. 3 Patients infected with the 027 strain are 3 times more likely to have severe disease than those infected with non-027 strains. 4,5 This finding was linked to increased production of A, B, and binary toxins, in association with a mutation in the gene regulating of the expression of these toxins, leading to overproduction.…”
Section: Hypervirulent Clostridium Difficile Strain Has Arrived In Brmentioning
confidence: 99%
“…lostridium difficile is a leading cause of nosocomial antibioticassociated diarrhea in developed and developing countries (1,2,5). Antibiotic treatment results in disturbance of the natural gut microflora, allowing germination and outgrowth of C. difficile spores and proliferation and colonization of live cells (3).…”
mentioning
confidence: 99%
“…nfections caused by Clostridium difficile are the leading cause of nosocomial antibiotic-associated diarrhea in developed and developing countries (1,2). Mortality rates of C. difficile infections (CDIs) may reach up to 5%; however, the recurrence of the infection, which may reach up to 25, 40, and 65% of cases after a first, second, and third episode of CDI, respectively, has become the current main clinical challenge (3).…”
mentioning
confidence: 99%